Analisis Kebutuhan Pangan Mendukung Percepatan Diversifikasi Pangan di Nusa Tenggara Timur dan Maluku - Maesti Mardiharini (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
Assessment on Properties of Innovation Technology Component to Determine Dissemination Patter in East Nusa Tenggara and Maluku. To support the development of  food diversification in Indonesia need an integrated effort  from different stakeholder,  include technology availability from Indonesia agency for Agriculture Research and Development (IAARD). The objective of  this study was : (1) to identify the prerequisite in the effort  of accelerate  food diversification aplication, (2) to analyze  the government policies, especially in local contect, that  supported food diversification program, and (3) to formule the strategy in technology development, especially by the Institute for Agricultural TechnologyAssessment (BPTP), in the progress of accelerated food diversification aplication. The Study conducted in the province of East Nusa Tenggara and Maluku . Data collection was through Participatory Rural Appraisal ( PRA ) approach. The main result of the study showed, adequate alternative food was available , but the process and storage technologies have not been optimally supported. The development of alternate food is availaable and need supporting system in technology dissemination and social engineering. In the development process still lack of synergi between  the  traditional  institutions with institutional that  formulate by  the government. Need a special study of the role of the church (in the case of NTT) and traditional institutions (in the case of Maluku) in the efforts of accelerate the aplication of  food  diversification and government role in institution development.  In the local contect, there is no policy support in the form of Regulation that directly support the development of food diversification  aplication. IAAT through their assessment result need to advocate the urgency of local government support in food diversification aplication  through regulation. In the future needs a special study of the diversification requirements , namely : the availability and distribution of food , availability of technology , and social culture. AIAT also need to make specific recommendations to the local government in implementing the regulation and  Ministry of agriculture regulation in relation with food diversification. Based on these study results, the role of IAAT in  diversification development not only in the internalization of diversification of food consumption, but also in business  and local food industry development.M Field School is one of the strategic programs of the Ministry of  Key words: Agricultural innovation, diversification, status and acceleration ABSTRAK Upaya diversifikasi pangan perlu lebih serius dan terintegrasi melibatkan semua pihak terkait, termasuk peran Badan Litbang Pertanian yang terkait dengan penyiapan inovasi pertaniannya. Tujuan kajian ini adalah: (1) mengidentifikasi status prasyarat percepatan diversifikasi pangan; (2) menganalisis kebijakan pemerintah (daerah) mendukung program diversifikasi pangan; dan (3) merumuskan strategi pengembangan inovasi pertanian, terutama oleh Balai Pengkajian Teknologi Pertanian (BPTP) ke depan dalam mendukung percepatan diversifikasi pangan. Lokasi kajian di Provinsi Nusa Tenggara Timur dan Maluku, melalui pendekatan Participatory Rural Appraisal (PRA). Hasil kajian antara lain menunjukkan bahwa pangan alternatif tersedia secara memadai, namun teknologi pengolahan dan penyimpanan belum mendukung secara optimal, murah, mudah dan cepat. Pengembangan pangan alternatif cukup potensial dan kondusif, namun dibutuhkan percepatan diseminasi dan rekayasa sosial. Belum ada sinergi antara kelembagaan bentukan masyarakat dengan kelembagaan bentukan pemerintah. Perlu kajian khusus terhadap peran gereja (kasus di NTT) dan lembaga adat (kasus di Maluku) dalam mendukung upaya percepatan diversifikasi dan kaitannya dengan berbagai lembaga bentukan dari atas. Sejauh ini, belum ditemukan adanya dukungan kebijakan dalam bentuk Peraturan Daerah (Perda) khusus tentang pengembangan diversifikasi pangan di kedua wilayah yang diamati. BPTP di wilayah terkait diharapkan dapat melakukan advokasi, dengan dukungan hasil pengkajian tentang perlunya PERDA mendukung diversifikasi pangan. Perlu ada kajian khusus tentang prasyarat diversifikasi pangan, yaitu: ketersediaan dan distribusi pangan, ketersediaan teknologi; dan sosial budaya masyarakat. BPTP juga perlu membuat rekomendasi spesifik lokasi kepada PEMDA dalam menerapkan Perpres dan Permentan. Berdasarkan hasil kajian tersebut, maka fungsi dan peran Badan Litbang Pertanian di daerah (melalui BPTP), tidak saja dalam internalisasi penganekaragaman konsumsi pangan, tetapi juga dalam pengembangan bisnis dan industri pangan lokal. Kata kunci: Inovasi pertanian, diversifikasi pangan, status dan percepatan